THE ISSUE OF HARMONY IN CENTRAL ASIAN ARCHITECTURE - Sherova Dilorom Abdullaevna (Scholar Express Journal, 2023)
In this article, the author analyzes the specific scientific and spiritual law of medieval oriental architecture, as well as the similarity of building methods and the peculiarities of architectural style and artistic symbols, creating a form that ensures the harmony of shapes and is the basis for geometric analysis. The differences and similarities of ancient monuments in Uzbekistan are also shown. In particular, the constructions of ancient buildings in Shakhrisabz, Samarkand and Khorezm
Keywords: Art; architecture; harmony; building decorations,